Pengaruh Gas Etilen Strawberi (Fragaria L.) terhadap Pertumbuhan Tinggi Batang Tanaman Kacang Hijau (Vigna radiata L.) - Tahri; Savira Hidayanti; Laila Rahma Zahranie (Jurnal Biologi dan Pembelajarannya (JB&P), 2023)
This study aims to determine the effect of ethylene gas contained in strawberries (Fragaria L.) on the tall stems of green bean plants (Vigna radiata L.). In this study the method used is experimental research. This study provides 3 different treatments on green beans. Treatment 1 was used as a control, treatments 2 and 3 used 1:5 strawberries. The results of this study show the effect of ethylene gas on strawberries on the growth of green bean stems.